Comprehensive analysis of androgen receptor status in prostate cancer with neuroendocrine differentiation - Su, Ruopeng; Chen, Lei; Jiang, Zhou; Yu, Minghao; Zhang, Weiwei; Ma, Zehua; Ji, Yiyi; Shen, Kai; Xin, Zhixiang; Qi, Jun; Xue, Wei; Wang, Qi (Frontiers in Oncology, 2022)
The androgen receptor (AR) signaling is a key contributor to tumorigenesis and progression of prostate cancer. A subset of patients may develop neuroendocrine (NE) features, resulting in resistance to androgen deprivation therapy and poor prognosis. In this study, we combined immunostaining, bulk and single-cell transcriptome analyses to better characterize the status of AR in prostate cancer with neuroendocrine differentiation. The exploration of online datasets indicated the existence of ARHIGH/NEHIGH prostate cancer and revealed that these double-high cases are majorly present in castration-resistant prostate cancer with a less neuroendocrine transdifferentiated state. We then reviewed 8194 prostate cancer cases with available immunohistochemistry reports and found 2.3% cases (n=189) showed at least one of the NE markers (chromogranin A, synaptophysin, and neural cell adhesion molecule 1) positive in at least 5% of epithelial cells. Within these 189 cases we observed that 81.0% cases (n=153) showed AR positive and 19.0% (n=36) showed AR negative. Patient with AR loss tumors demonstrated a correlation with adverse clinical stages, indicating a trade-off between AR and advanced disease in neuroendocrine differentiation. Using multiplex immunofluorescence staining, we observed the co-localization of AR and NE markers in prostate cancer cells. In addition, data mining of single-cell transcriptome further confirmed the existence of ARHIGH/NEHIGH prostate cancer cells in castration-resistant samples and suggested AR still exerts its androgen response and anti-apoptotic effect in these double-high cells. Thus, our study provides a better understanding of AR signaling in the cellular plasticity of prostate cancer with neuroendocrine differentiation and allows new insights into the therapeutic development.